Chronic fetal hypoxia and antenatal Vitamin C exposure differentially regulate molecular signalling in the lung of female lambs in early adulthood - McGillick, Erin V.; Orgeig, Sandra; Allison, Beth J.; Brain, Kirsty L.; Bertossa, Melanie R.; Holman, Stacey L.; Meakin, Ashley S.; Wiese, Michael D.; Niu, Youguo; Itani, Nozomi; Skeffington, Katie L.; Beck, Christian; et al. (Frontiers in Physiology, 2025)
IntroductionChronic fetal hypoxia is commonly associated with fetal growth restriction and can predispose to respiratory disease at birth and in later life. Antenatal antioxidant treatment has been investigated to overcome the effects of oxidative stress in utero to improve respiratory outcomes. We aimed to determine if the effects of chronic fetal hypoxia and antenatal antioxidant administration persist in the lung in early adulthood.MethodsChronically catheterised pregnant sheep were exposed to normoxia (N; n = 20) or hypoxia (H; n = 18; 10% O2) ± maternal daily i. v. saline (N = 11; H = 8) or Vitamin C (VC; NVC = 9; HVC = 10) from 105 to 138 days (term, ∼145 days). Lungs were collected from female lambs 9 months after birth (early adulthood). Lung tissue expression of genes and proteins regulating oxidative stress, mitochondrial function, hypoxia signalling, glucocorticoid signalling, surfactant maturation, inflammation and airway remodelling were measured.ResultsChronic fetal hypoxia upregulated lung expression of markers of prooxidant, surfactant lipid transport and airway remodelling pathways in early adulthood. Antenatal Vitamin C normalized prooxidant and airway remodelling markers, increased endogenous antioxidant, vasodilator and inflammatory markers, and altered regulation of hypoxia signalling and glucocorticoid availability.ConclusionThere are differential effects of antenatal Vitamin C on molecular markers in the lungs of female lambs from normoxic and hypoxic pregnancy in early adulthood.